Ausdehnung einiger Sätze von Aksentjeff und Tshakaloff auf die Klassen Kn(D) - Kirjatsky, E. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Э. Г. Кирьяцкий. Распространение некоторых теорем Аксентьева и Чакалова на класс Kn(D) E. G. Kirjackis. Kai kurios Aksentjevo ir Čakalovo teoremos Kn(D) klasėje